Sobre el realisme històric i el teatre-document (o de quan els autors estudiaven Història) - Rosselló, Ramon X. (Caplletra. Revista Internacional de Filologia, 2000)
Resum: This essay attempts to approach the Catalan theatrical production of the 1960s and 70s related to the theatredocument, with special emphasis on M. Aurèlia Capmany and X. Romeu’s «Qüestions and answers about the Ufe and death of Francesc Layreu lawyerfor the workers of Catalonia» (1970), one of the most outstanding examples of this theatrical formula. Paraules clau: realisme històric; teatre-document; teatre català; anys seixanta i setanta; M. Aurèlia Campmany; Xavier Romeu